การบังคับใช้พระราชบัญญัติป้องกันและปราบปรามการค้ามนุษย์ พ.ศ. 2551 : ศึกษากรณีการให้ความคุ้มครองผู้เสียหายที่จะไม่ถูกดำเนินคดี - กัมปนาท ณ วิชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Human trafficking is currently taken into account by global community as one of the significant hindrances to a fundamental right of a human, and also an irrefutable demotion of human’s dignity. Such predicament has been progressively more severe, literally relentless, as human is an indispensable essence of social foundation as well as an inheritor of amassed traditional and cultural values which render the ongoing conservation of society. Nevertheless, an attempt of the human to take advantages from one another by any means through physical force, corporeal duress, intimidation, abduction and/or deceptive beguilement just to seduce any other humans into prostitution, labor exploitation and/or slavery. The mistaken and iniquitous manipulation of another human’s social inferiority to immorally and unlawfully promote self-interest is believed to be an annihilation of human’s value and spirit. This thesis largely portrays the protective process conducted on victims who are not to be put on trial for the charge of human trafficking. By considering on willingness or participation on guilt of innocent victim following legislation only. Thus, this research intends to propose that in other words the term of ‘innocent victim’ should be clearly defined and be categorized into detailed categories. No more than victims who are truly innocent and are themselves victims aimlessly, deceptively and unwillingly deluded to human trafficking correlated course of action should be protected by the mentioned Act. The Act should furthermore be amended to be in conformity with the international commitment aimed at protecting rights of the victims suffered from human trafficking. The Act should as well protect and provide appropriate assurance and security for victims. This will in turn ameliorate substructure of human trafficking related law which is of great magnitude for the judicial process of Thailand.